Safety in the skies : personnel and parties in NTSB aviation accident investigations - Lebow, Cynthia C.; Sarsfield, Liam, 1955-; Stanley, William L.; Ettedgui, Emile; Henning, Garth; Rand eBooks (Santa Monica, CA : RAND, 1999)
The National Transportation Safety Board (NTSB) bears a significant share of the responsibility for ensuring the safety of domestic and international air travel. The NTSB relies on teamwork to resolve accidents; the "parties" that participate in an investigation may include manufacturers and operators, as well as the Federal Aviation Administration. This arrangement works well under most circumstances, despite inherent conflicts of interest that may jeopardize, or be perceived to jeopardize, the integrity of the NTSB investigation. The NTSB's ability to lead investigations and to form expert teams is also seriously threatened by a lack of training, equipment, and facilities; by poor control of information; and inadequate aids to project management. Additionally, the need to modernize investigative practices and procedures is particularly acute. In this report, RAND outlines a comprehensive set of recommendations intended to help the NTSB strengthen the party process, create a more expansive statement of causation, modernize investigative procedures, streamline internal operating procedures, better manage resources, maintain a strategic view of staffing, streamline training practices, improve facilities for engineering and training.
"Institute for Civil Justice."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: United States. -- National Transportation Safety Board -- Evaluation; Aircraft accidents -- Investigation -- United States; Conflict of interests -- United States; Electronic books